Theorizing the 'indies' : the market place, ideology and the new Malaysian cinema / Mahyuddin Ahmad - Ahmad, Mahyuddin (UPENA, 2008)
John Hill (1986) argues that cinema is not just simply an economic industry. In his work on British Cinema, he emphasizes that we need to understand the idea of the relations of production or the political economy of the industry in which the products are produced. The film industry we had earlier (circa 1930s - 1970) was one of the main culture industries in Malaysia. The industry however is a structure that comes out of a competitive liberal market, which in turn is due to the expansion of capitalism and the process of colonization. This paper argues that film industry is an economic institution and in the case of the Malaysian film industry, economy was a crucial factor which determined its development. Another essential factor is the function of the state in regulating and controlling the industry. In a neo-capitalist state like Malaysia, the interplay between capitalism and its forces, the function of the state, and the legacy of the dominant ideology are important and should not be underestimated and I would argue that any analysis of Malaysian cinema must be located within and grounded on a wider analysis of the capitalist economic and social system, politics and the role of the state. Based on this line of argument this paper is set to examine and locate the film industry against the historical background which gives rise to a new kind of direction and a new form of cinema, loosely termed as the 'independent' production. The term 'independent' however, seems to be problematic. With the new kind of development in the industry that happened in the last 5 years or so, spearheaded by the production of short films and feature films that are 'different' in comparison to the mainstream production, the term 'indies' has changed significantly.